MIXING CYRILLIC AND LATIN IN MEDIA TEXTS: PROBLEMS OF STYLE, GRAPHICS, AND SPELLING - Bybyk, Svitlana (Linguistic Bulletin (Movoznavchyi Visnyk), 2024)
Introduction. The article analyzes the factors causing the spread of barbarism in the Ukrainian literary language, in particular in the texts of the media environment. The relevance of the study is determined by the need to update the theoretical foundations of the normalization of the Ukrainian literary language, to understand the challenges of the linguistic present, in particular the Latinization of book practice - officialbusiness, scientific-educational, media and private communication. It is emphasized that barbarization is one of the manifestations of globalization processes of communication and information exchange between institutions, organizations, media, communities, individuals, as well as a consequence of the hybridization of certain linguistic phenomena. It is not new and has been covered in numerous studies on the history of the Ukrainian literary language. One of the aspects of this direction of studying dynamic changes in book language practice is the mixing of Cyrillic and Latin graphics, and accordingly, the lexicons of specific languages. Factors of the genesis of the Ukrainian literary graphic-orthographic-lexical tradition are the extra- and intralingual prerequisites for convergence and distancing of languages. The purpose. The purpose of the research is to outline the range of problems of the culture of the Ukrainian language, media stylistics and sociolinguistics, which in close interaction determine the latest theoretical and practical aspects of mixing Cyrillic and Latin in the modern media space; outline the directions of actualization of barbarization. The methods. The main research method is descriptive and methods of observation, generalization, and comparison. Main results of the study. Based on the material of the texts of the media sphere from 2020 to 2024, conclusions are made about the effectiveness of the digitalization of communication, the strengthening of transculturality in communication, about the polythematism of information from multilingual sources, which requires its unification, general accessibility to consumers, which together affect the establishment of norms regarding Latin-language or mixed writing in Usus names and unadapted phrases. As a result, it was noted that there are manifestations of dynamic chaos in the graphic and orthographic norm of the Ukrainian literary language. This phenomenon is caused by the search for a self-organized system of symbolic norms that would reflect both the literary book-writing tradition and reflect the modern perception of rapidly emerging proper names, words-terms, the rapid introduction and graphic adaptation of neologisms-borrowings in the Ukrainian linguistic system. Originality. For the first time in Ukrainian linguistics, the concepts of the dynamics of the language norm in the 21st century were formulated. Conclusions and specific suggestions of the author. The need to study the barbarization of Ukrainian book practice, taking into account extra- and intralingual factors affecting stylistics, graphics, orthography, and grammar of the Ukrainian literary language, is outlined as a perspective for further research.